Recovering lost time in Syria: a new Eocene stereogenyin turtle from the Aleppo Plateau - Alhalabi, Wafa Adel; Martucci Neto, Donato J.; Ferreira, Gabriel S.; Bou Jaoude, Issam; Naser, Hassan M.; Ayoub, Jouliana; Abboud, Lama; Shati, Rim; Koutsoukos, Eduardo A. M.; Langer, Max C. (Papers in palaeontology, 2025)
Across the Arabian Platform, fossil turtles have been recovered from deposits dating back to the Cretaceous. In Syria, such remains are mostly fragmentary, recovered from the phosphatic deposits around Palmyra, as well as from the Pleistocene Nadaouiyeh Aïn Askar archaeological site. Here we report a new genus and species, Syriemys lelunensis, represented by a fully preserved inner cast of the shell, plus some plastral, pelvic and hind-limb bones, some enclosed within the cast. The specimen was collected from the Al-Zarefeh Quarry, near Afrin, in Aleppo Governorate, with foraminifera extracted from the surrounding rock indicating an early Eocene age. Syriemys lelunensis can be ascribed to the pleurodiran clade Stereogenyini based on a short cranial lobe of the plastron, which does not extend beyond the cranial margin of the carapace, a short epiplastral symphysis, and very reduced gular, extragular and humeral scutes. Syriemys lelunensis also differs from all other known members of the group that have a preserved shell by the presence of three autapomorphic traits: seven neural bones extending at least to costal bone 7, a nuchal bone with a cranial edge half the lateromedial breadth of its widest part, and a shallow anal notch formed by short xiphiplastral processes. This discovery pushes the origin of Stereogenyini back at least to the early Eocene, providing further support for a Mediterranean ancestral geographical range for the group. Finally, Sy. lelunensis represents the first new species of extinct vertebrate ever described from Syria.